2014
DOI: 10.2337/db14-0858
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin-Specific, HLA-DQ8, and HLA-DQ8-Transdimer–Restricted CD4+ T Cells Infiltrate Islets in Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) develops when insulin-secreting b-cells, found in the pancreatic islets of Langerhans, are destroyed by infiltrating T cells. How human T cells recognize b-cell-derived antigens remains unclear. Genetic studies have shown that HLA and insulin alleles are the most strongly associated with risk of T1D. These longstanding observations implicate CD4 + T-cell responses against (pro)insulin in the pathogenesis of T1D. To dissect the autoimmune T-cell response against human b-cells, we isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
191
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 37 publications
7
191
1
1
Order By: Relevance
“…For example, the work by Kent et al (28) identified CD4 T cells responding to DR4-presented epitopes from the insulin A-chain. Another recent study has described a series of CD4 T-cell clones isolated from the pancreas of a T1D patient that is reactive to C-peptide epitopes presented by DQ8 or DQ8/DQ2 heterodimers (29). Unfortunately, unlike in the case of NOD mouse, the tools are presently lacking to determine the relative importance of these different antiinsulin responses in the onset and progression of the disease in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the work by Kent et al (28) identified CD4 T cells responding to DR4-presented epitopes from the insulin A-chain. Another recent study has described a series of CD4 T-cell clones isolated from the pancreas of a T1D patient that is reactive to C-peptide epitopes presented by DQ8 or DQ8/DQ2 heterodimers (29). Unfortunately, unlike in the case of NOD mouse, the tools are presently lacking to determine the relative importance of these different antiinsulin responses in the onset and progression of the disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…ELISPOT analyses were conducted as previously described using the human IFN-γ and IL-10 ELISPOT Kits (UCyTech Biosciences) (29). Details are discussed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The islet epitopes presented by HLA-DQ8trans are largely unknown. Importantly, HLA-DQ8cis/trans-restricted CD4 T-cell clones have been isolated from human insulitis lesions, and T-cell autoreactivity was confirmed for several proinsulin peptides, underscoring the potential relevance of preproinsulin (PPI) peptides presented by HLA-DQ in diabetogenesis (10)(11)(12)(13). We contend that knowledge of the HLA-DQ8trans islet peptidome provides insight in the mechanism by which HLA-DQ2/8 heterozygosity imposes excessive risk for T1D.…”
mentioning
confidence: 89%
“…1 and Table 1) were eluted with a mean peptide length of 14 amino acids (range [11][12][13][14][15][16][17][18][19]. All peptides are members of nested peptide sets covering three distinct core regions of the N-terminus of IA-2.…”
Section: Uptake Of Islet Antigens By Pulsed DCmentioning
confidence: 99%
“…NOD mice have also been informative about mechanisms that result in autoimmune diabetes, although it is unclear how these specifically contribute to disease pathogenesis in an individual human patient (1). Predisposing MHC genes, along with autoimmune reactions to insulin and its precursor proinsulin, are important in both mouse and human disease (2)(3)(4)(5)(6). Less clear is the value of animal models as part of the preclinical development of new treatments for disease.…”
mentioning
confidence: 99%